Peran Alam dalam Cerita Rakyat Bugis Makassar - Rapi, Muhammad; Nurhusna, Nurhusna (Nuances of Indonesian Language, 2024)
This research examines the role of nature in Bugis Makassar folklore. This research uses a qualitative approach to explore and understand the meaning contained in folklore. A literature study was used to collect references related to Makassar Bugis folklore and the study of nature in this culture. The data obtained used the thematic analysis method. The researcher identified the main themes that emerged from the data and grouped the information based on the relationship between natural elements and the moral values contained in the story. After the analysis was complete, the researcher interpreted the results and described how nature plays a role in the narrative structure of Makassar Bugis folklore. The research results reveal that natural elements are proven to have very significant and diverse functions in the narrative structure and in conveying the cultural values of the Bugis community. Through analysis of various folk tales, it was found that nature not only functions as a background but also as an active character, influencing the decisions and fate of the characters. Elements such as forests, rivers, and weather phenomena become symbols that reflect emotional states and morality and emphasize the importance of a harmonious relationship between humans and the environment. In the modern context, the importance of preserving folklore and the cultural values contained therein is increasingly relevant, especially in facing environmental challenges. Thus, a deep understanding of the role of nature in Bugis Makassar folklore can contribute to efforts to preserve culture and the environment amidst rapid societal development.